Razvijanje recepcijske zmožnosti pri otrocih z lažjo motnjo v duševnem razvoju - Koritnik, Ana (Revija za elementarno izobraževanje, 2015)
The paper presents research paradigms which study factors that allow influencing the language development of children with mild intellectual disabilities to the greatest extent possible. Special attention is dedicated to the development of the reception competence with the use of reception didactics methods based on a relatively frequent use of less demanding non-language semiotic functions. The core of the paper presents results of an experimental case study (on a sample of five children with a mild intellectual disability over a one school year period), through which the reception competence in these children was developed with a systematic use of an adapted communication model of literary education as an experimental factor. The results have confirmed the initially set hypothesis about reception progress.
Keywords: recepcijska didaktika; reception didactics; reception competence development; otroci s posebnimi potrebami; motnje v duševnem razvoju; children with a mild intellectual disability; jezikovni razvoj; language development; učne metode